2023
DOI: 10.3389/fpubh.2022.981136
|View full text |Cite
|
Sign up to set email alerts
|

Escaping negative moods and concentration problems play bridge roles in the symptom network of problematic smartphone use and depression

Abstract: BackgroundProblematic smartphone use (PSU) has become an issue of great concern in the age of smartphones. PSU is associated with emotional problems, one of which is depression, as shown by empirical studies. However, previous studies have been limited in that they have focused solely on the total score for symptoms of PSU and depression while ignoring the symptomatic heterogeneity of these two concepts.MethodThis study filled this gap by exploring links between symptoms of PSU and depression among 1,849 unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“… 28 According to compensatory network use theory, mobile phones and the Internet can be used as a way of compensating for negative emotions in adolescents, but the failure of self-control in the use of mobile phones was positively correlated with MPD. 29 In addition, direct and indirect evidence for learning burnout and MPD in adolescents has been provided by previous studies. Direct evidence comes from Zhang et al 30 study of 1475 adolescents in China, which showed that MPD was a direct predictor of learning burnout.…”
Section: Introductionmentioning
confidence: 94%
“… 28 According to compensatory network use theory, mobile phones and the Internet can be used as a way of compensating for negative emotions in adolescents, but the failure of self-control in the use of mobile phones was positively correlated with MPD. 29 In addition, direct and indirect evidence for learning burnout and MPD in adolescents has been provided by previous studies. Direct evidence comes from Zhang et al 30 study of 1475 adolescents in China, which showed that MPD was a direct predictor of learning burnout.…”
Section: Introductionmentioning
confidence: 94%
“…Prolific smartphone use can also deteriorate sleep quality, indirectly increasing the risk of depression ( 59 ). A study indicates that over-reliance on smartphones might be a strategy driven by an escapist motive linked to depression ( 60 ). However, most studies focus primarily on adolescent populations, and many of the findings are indirect, which imposes certain limitations on the research methods.…”
Section: Discussionmentioning
confidence: 99%
“…La adicción a los teléfonos inteligentes y los síntomas depresivos son dos problemas prevalentes y altamente correlacionados entre los estudiantes universitarios (Shi et al, 2023), aspectos que se ven reflejados en los resultados de este trabajo, al vincularse el uso del teléfono móvil con un estado emocional, convirtiendo el móvil en una herramienta para enfrentarse a estados emocionales desagradables, al usarse cuando se sienten solos (66%) o cuando se siente mal (32.3%), siendo estos resultados coincidente con los de otros trabajos (Romero y Aznar, 2019;Echeburúa, 2012;Pourafshari et al,2022;Wei et al,2023).…”
Section: Discussionunclassified